2020
DOI: 10.1021/acs.macromol.9b02267
|View full text |Cite
|
Sign up to set email alerts
|

Nonionic Water-Soluble and Cytocompatible Poly(amide acrylate)s

Abstract: We report secondary amide side-chain-bearing polyacrylates with tunable aqueous solubility and cellular interaction. Redox-initiated reversible addition-fragmentation chain transfer polymerization of methylamide ethyl acrylate (MAmEA) and ethylamide ethyl acrylate (EAmEA) yielded well-defined homopolymers. P(MAmEA) and P(EAmEA) possess high glass-transition temperatures compared to the equivalent alkylated polyacrylates. P(EAmEA) showed a degree of polymerization and concentration-dependent lower critical solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…P(E 1 ) is highly negatively charged due to the carboxylic acid groups (Table S3), while P(EAmEA), with its terminal ethyl amide side groups, is a nonionic polymer. 42 Moreover, when the experiment was performed at 4 °C, P(EAmEA) association with 3T3 cells was substantially inhibited in comparison to P(E 1 ). Thus, it can be concluded that the type of side chain significantly affects the cellular uptake mechanisms of the resulting polymers.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…P(E 1 ) is highly negatively charged due to the carboxylic acid groups (Table S3), while P(EAmEA), with its terminal ethyl amide side groups, is a nonionic polymer. 42 Moreover, when the experiment was performed at 4 °C, P(EAmEA) association with 3T3 cells was substantially inhibited in comparison to P(E 1 ). Thus, it can be concluded that the type of side chain significantly affects the cellular uptake mechanisms of the resulting polymers.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…Subsequently, the ethyl (N-propionyl) side chain and acrylate functionality were introduced through amidation and esterification, respectively, as reported for their amide equivalents. 42 The same sequence of reactions was repeated using E 1t instead of tert-butyl acrylate to obtain E 2t . Noteworthy, the choice of solvent for the reaction of ethanolamine with E 1t was critical.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tertiary amide alcohol was previously synthesized and then esterified by (meth)acryloyl chloride. The same strategy was employed to synthesize secondary amide acrylate in the recent work by Mahmud et al 27 Because the tertiary amide moiety is deemed the repeating unit of POXs, functionalization from 2-oxazolines seems feasible by combining the chemical properties of 2- oxazolines. Weber 28 reported three routes to functionalize (meth)acrylate with POX units with 2-oxazolines.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…For LCST behavior in particular, the hydrophilic–hydrophobic balance in the polymer structure can be carefully optimized to tune the LCST behavior, or more specifically, the phase separation temperature or the cloud point temperature (T cp ) at a given polymer concentration. In this regard, numerous hydrophilic–hydrophobic monomer combinations have been explored for several biocompatible polymer classes, such as poly(acrylamides) [ 15 , 16 , 17 ], oligoethyleneglycol functional polymers [ 10 , 18 , 19 ], poly(amino acids), polypeptoids, and poly(2-alkyl-2-oxazoline)s (PAOx) [ 20 , 21 , 22 , 23 , 24 ], and they are subsequently exploited in tissue engineering or drug delivery contexts [ 25 , 26 , 27 , 28 , 29 , 30 ]. While tuning the LCST behavior by varying the relative ratio of hydrophilic to hydrophobic monomers might seem straightforward, several factors have to be taken into account, viz.…”
Section: Introductionmentioning
confidence: 99%